Constraining climate sensitivity and continental versus seafloor weathering using an inverse geological carbon cycle model - Joshua Krissansen-Totton (Nature Portfolio, 2017)
The influence of tectonics, continental weathering, and seafloor weathering in the geological carbon cycle remain unclear. Here, the authors develop a new carbon cycle model and, through comparison with proxy data, critically evaluate the influence of these components on carbon fluxes since 100 Ma.